Pathway to Increase Standards and Competency of eDNA Surveys (PISCeS)—Advancing collaboration and standardization efforts in the field of eDNA. Issue 3 (22nd June 2020) - Loeza‐Quintana, Tzitziki; Abbott, Cathryn L.; Heath, Daniel D.; Bernatchez, Louis; Hanner, Robert H.
Abstract: This special issue features eleven articles presented at the Pathway to Increase Standards and Competency of eDNA Surveys (PISCeS) conference in October 2018. The prominent theme in this special issue is methodological developments to enhance species and community characterization using eDNA, covering tree main scientific trends: validation of eDNA detections, methodological innovations in eDNA research, and standardization of eDNA practices. Articles in this special issue cover advances on single‐species detection and metabarcoding, and examine eDNA methods standardization. Strong collaboration among academics, regulators, and industry present in the eDNA community is evidenced by the research presented here. Abstract : This special issue features eleven articles presented at the Pathway to Increase Standards and Competency of eDNA Surveys (PISCeS) conference in October 2018.